Nitric oxide synthase-dependent immune response against gram negative bacteria in a crustacean, Litopenaeus vannamei. (March 2016) - Rodríguez-Ramos, Tania; Carpio, Yamila; Bolívar, Jorge; Gómez, Leonardo; Estrada, Mario Pablo; Pendón, Carlos
Abstract: Nitric oxide (NO) is a short-lived radical generated by nitric oxide synthases (NOS). NO is involved in a variety of functions in invertebrates, including host defense. In previous studies, we isolated and sequenced for the first time the NOS gene from hemocytes of Panulirus argus, demonstrating the inducibility of this enzyme by lipopolysaccharide in vitro e in vivo . Hyperimmune serum was obtained from rabbits immunized with a P . argus –NOS fragment of 31 kDa produced in Escherichia coli, which specifically detected the recombinant polypeptide and the endogenous NOS from lobster hemocytes by western blotting and immunofluorescence. In the present work, we demonstrate that the hyperimmune serum obtained against P . argus NOS also recognizes Litopenaeus vannamei NOS in hemocytes by western blotting and immunofluorescence. Our data also show that while the hemolymph of L . vannamei has a strong antibacterial activity against the Gram negative bacteria Aeromonas hydrophila, the administration of the anti NOS serum reduce the natural bacterial clearance. These results strongly suggest that NOS is required for the shrimp immune defense toward Gram negative bacteria. Therefore, the monitoring of induction of NOS could be an important tool for testing immunity in shrimp farming. Highlights: Polyclonal serum against P . argus NOS also recognizes L . vannamei NOS in hemocytes. This polyclonal serum against NOS was able to reduce NOS activity in vivo in L . vannamei This antibody or a chemical NOS inhibitor reduced the hemolymph antibacterial activity. The results indicate that NOS is required for the shrimp defense toward Gram− bacteria.